KEMAMPUAN BERPIKIR KREATIF PADA PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN METODE DRILL - Nur Hayati; Novi Marliani (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2018)
The purpose of writing this kel meaning is so that we can know and apply the drill method in the teaching and learning process in an effective teaching. If we want to produce something or a learning system that is good and in accordance with what is expected, it must have effective and creative learning by applying the method. While the teaching method is said to be efficient if its application in producing something expected is relatively using energy, effort, expenditure, and minimum time or the smaller the energy, effort, cost, and time spent the more efficient the method. The method in writing this article is by literature study. The results obtained are in the form of writing exposure to creative thinking skills in mathematics learning using the drill method.